Financial integration in the GCC region: market size versus national effects - Kerim Peren Arin; Guglielmo Maria Caporale; Kyriacos Kyriacou; Nicola Spagnolo (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper examines financial spillovers between the four largest equity markets (by market capitalization) in the GCC region using a VAR-GARCH (1,1) framework that sheds light on interdependence as well as the effects of the 2014 oil crisis. Since the UAE is a federation including two stock exchanges (Abu Dhabi and Dubai), it is possible to test whether being part of a federal union matters more than market size in terms of financial integration. Our results suggest that the latter is more important, since we could not find evidence of stronger linkages between the Abu Dhabi and Dubai markets compared to those between other markets in the region. By contrast, there are significant spillover effects, both in the mean and in the volatility, from the largest market of Saudi Arabia to Qatar and the two markets in the UAE, which confirms that market capitalization is a more important determinant of financial integration than belonging to a federal union. Further, spillovers from the larger markets have become stronger as a result of the 2014 oil crisis. Finally, there is also evidence of spillovers from the smaller to the larger markets.
Keywords: C32; F36; G15; 330; stock markets; GCC; volatility transmission